An Error Analysis of Paragraphs Written by English Language Education Freshmen at Universitas Negeri Makassar - Bakir, Muh. Anas; Korompot, Chairil Anwar; Sofyan, Ryan Rayhana (Program Studi Pendidikan Bahasa Inggris FBS UNM, 2025)
The study aimed to discover (1) The errors in the paragraph by English Language Education Freshmen based on the taxonomy by Dulay, Burt, and Khan (1982), which is surface strategy taxonomy, and (2) The factors influencing students’ errors based on their perceptions. This study employed qualitative than used descriptive methods. Google Forms and Interviews were used as the instruments to collect the data. Ten students were selected as participants by using a purposive random sampling technique. Eventually, this study showed that the types of errors made by students in their writing consist of omission of suffix “-s, -ing”, omission of apostrophes, omission of pronouns, omission of a verb, the addition of the suffix “-es”, the addition of verb, the addition of conjunction, the addition of pronoun and addition of noun phrase, misformation of verbs, misformation of noun, misformation of pronoun, misformation of noun phrase, contraction, and misformation of preposition. Then, students’ errors were influenced by some factors, namely incomplete comprehension, unconducive environment, unfocus, short time, lack of practice, inappropriate media, mother tongue, and incomprehension use of grammar.